Vanadium oxide supported on mesoporous SBA-15 modified with AI and Ga as a highly active catalyst in the ODS of DBT. - Rivoira , Lorena Paola; Martínez , María Laura; Anunziata , Oscar Alfredo; Beltramone, Andrea Raquel; Beltramone, Andrea Raquel; Anunziata , Oscar Alfredo; Martínez , María Laura (Universidad Tecnológica Nacional., 2017)
Vanadium oxides supported on mesoporous SBA-15 catalysts with different vanadium loadings were studied in the oxidative desulfurization (ODS) of dibenzothiophene as a model sulfur compound. The catalytic activity was improved when SBA-15 framework was modified by adding Al and Ga. Structural and textural characterization of the catalysts were performed by means of XRD, N2 adsorption, UVeVis eDRS, XPS, NMR, TEM, Raman, TPR and Py-FTIR. UVeViseDRS and Raman demonstrated that highly dispersed vanadium VO—3 species are responsible for the high activity in the sulfur removal. The Ga modified support with an intermediate V/Si ratio of 1/30 was the most active catalyst for ODS of DBT, using hydrogen peroxide as oxidant and acetonitrile as solvent. 100% of DBT elimination was attained at a short time in mild conditions. Gallium and aluminum incorporation into the support modified suc cessfully the nature of the SBA-15 surface by generating Bronsted and Lewis acidity. The interaction between the acid sites with the active vanadium sites improved the activity of the catalysts. The high dispersion depended on the vanadium loading and on the nature of the support. The more acidic support allowed better dispersion of the vanadium species due to stronger interaction metal-support. The reusability of the catalysts indicates that vanadium oxide supported on mesoporous SBA-15 modified with Ga and Al are potential catalysts for the ODS of dibenzothiophene.
Keywords: VOx supported SBA-15; Dibenzothiophene; Ultra-low-sulfur diésel; Deactivation; Gallium; Aluminum